The Influence Of Traditional Games On Improving Basic Movement Patterns In Physical Education Learning - Finny Rohaeni; Robby Dzulfaqor Noor; Yerdi Pratama; Adang Sudrazat (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to determine the effect of traditional games on improving students' basic movement patterns. The method used is pre-experimental. The population of this research is class V students at State SDN Bangkir for the 2023/2024 academic year. The instruments used are motor ability tests including the 30 m running test, shuttle run test, ball tag throwing test, and stork stand test. The data analysis technique was carried out using the t test and regression test using the SPSS For Windows 20 application, at the t test level the value of Sig was significant. (2tailed) < 0.05 based on data analysis, this research shows that there is an influence of traditional games on improving students' basic movement patterns of Sig. 0.000 < 0.05 and the magnitude of the influence of traditional games on improving students' basic movement patterns has a presentation of 86.8%. So it can be concluded that traditional games have an influence on improving the basic movement patterns of state students SDN Bangkir